PENGGUNAAN MODEL VALUE CLARIFICATION TECHNIQUE (VCT) PERCONTOHAN UNTUK MENINGKATKAN PROSES PEMBELAJARAN TEMATIK TERPADU DI KELAS IV SEKOLAH DASAR - Witia Audina; Reinita Reinita (Jurnal Bahana Manajemen Pendidikan, 2019)
This research was conducted based on the facts indicating that the integrated thematic     learning was not run as it was expected. The teacher seemed to ignore the involvement of the students in  applying each of the values obtained in a learning stimulus in the form of a theacher’s demonstration. The purpose of   this research  was  to  describe the application  of VCT Percontohan approach  in integrated thematic learning process. This research is a class action. This research was conducted at SD Negeri 15 Ulu Gadut Kota Padang. The subject of the research was the teacher and the students of class IV totaling 25 people . The result of the research revealed that the quality of integrated thematic learning increased. The first cycle of meetings one aspect of teacher 84,4 % (B) and 84,4 %(B) of student aspects, second meeting aspect teacher 90,62 % (SB) of the students aspect of90,62% (D). The second cycle of meetings one aspect of teacher 93,75% (SB) of the student aspect 93,75% (SB).